«Дожити до ста»: моделювання героя в романі Володимира Лиса Століття Якова - Krupka, Liubomir (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The article is devoted to the study of the novel by Vladimir Fox, The Age of Jacob. The main purpose is to analyze ways of modeling identity in the context of the axiological priorities of the protagonist as a collective image of the Ukrainian peasant in the 20th century.